A Case Report of Extensive Cerebral Venous Sinus Thrombosis as a Presenting Sign of Relapsing Nephrotic Syndrome - Janet K. Lee; Kathleen Murray; Swetha Renati (Case Reports in Neurological Medicine)
Nephrotic syndrome is defined by three characteristic features including proteinuria of >3 g in 24 hours, hypoalbuminemia of less than 3 g/dL, and peripheral edema. Multiple nephropathies can result in nephrotic syndrome. Most commonly, minimal change disease is seen in children under the age of 10, while adults are more commonly found to have membranous nephropathy. Hypercoagulability and thrombotic sequela can be seen in nephrotic syndrome, regardless of underlying etiology, and thrombosis is most commonly seen in deep veins of the lower extremities and renal veins. Our case identifies an adult with previously diagnosed and treated for minimal change disease who presented with weight gain, peripheral edema, foamy urine, headache but no neurologic deficits. The patient was found to have near to complete occlusion of the entire superior sagittal sinus, near complete occlusion of the left transverse and sigmoid sinuses, and nonocclusive thrombus in the right sigmoid sinus. She was treated with heparin and IV steroids then transitioned to warfarin and PO steroids, respectively, with resolution of symptoms. This case report emphasizes on the importance of recognizing CVST as a potential complication of nephrotic syndrome at both initial presentation and relapse.